Enhancing adult hippocampal neurogenesis with lysophosphatidic acid: a proposal for erasing cocaine contextual memory - Ladrón de Guevara-Miranda, David; Moreno-Fernández, Román D.; Gil Rodríguez, Sara; Rosell-del-Valle, Cristina; Estivill-Torrús, Guillermo; Serrano, Antonia; Pavón-Morón, Francisco Javier; Rodriguez-de-Fonseca, Fernando; Santín-Núñez, Luis Javier; Castilla-Ortega, María Estela (My University, 2018)
Stimulating adult hippocampal neurogenesis (AHN) has been uncovered as a promising approach in the manipulation of retrograde memories. This work aims to study whether increasing AHN with lysophosphatidic acid (LPA, an endogenous lysophospholipid with proneurogenic actions) promotes the forgetting of previously established cocaine-contextual associations. C57BL/6J mice previously trained in a cocaine-induced conditioned place preference (CPP) paradigm were submitted to 23 days of withdrawal, during which they received repeated intracerebroventricular infusions of LPA, ki16425 (a selective LPA1/3 receptors antagonist), or vehicle solution. Then, CPP maintenance was assessed, and the causal role of AHN in this process was evaluated using a mediation analysis. In a complementary experiment, wild-type and LPA1-null mice were acutely infused with LPA or ki16425 to determine the involvement of the LPA1 receptor in the in vivo proneurogenic actions of LPA. The chronic LPA treatment significantly weakened the long-term retention of a previously acquired cocaine-CPP memory, an effect clearly mediated by a LPA-induced increase in the number of adult-born dentate granule cells. In contrast, the ki16425-treated mice displayed aberrant responses of initially decreased CPP retention that progressively increased CPP across the extinction sessions, in absence of effects on AHN. The histological studies suggested that the proneurogenic actions of LPA were related to the enhancement of cell proliferation and critically depended on the LPA1 receptor function. Our results suggest that the LPA/LPA1-pathway acts as a potent in vivo modulator of AHN, and highlight the usefulness of a post-learning increase of adult-born hippocampal neurons as a strategy to promote the forgetting of cocaine-context associations.
Keywords: Neurogénesis; Memoria; Conditioned place preference; LPA1 receptor; Antagonist ki16425; Anxiety; Causal mediation analysis